Reducing the impact of the sunlight in urban areas using asphalt mixtures with phase change materials: a review in Scopus in the last three years - Landi Jr., Salmon (2022)
Phase change materials (PCMs) have been incorporated into asphalt concrete pavements because they can regulate the temperature by absorbing and releasing heat during physical state changes. This effect reduces temperature gradients of pavements and, consequently, increases its service life. This work presents a systematic review of recent articles published in peer-reviewed journals (available in the Scopus database) involving asphalt mixtures with PCMs and focusing on mechanical characterization. It is observed that most of the selected papers investigated the benefits of polyethylene glycol as a PCM. The most common strategy to avoid leakage during the phase transition involved using a porous material that acts as a carrier matrix for the PCMs. Generally, asphalt pavements with PCMs are systems with favourable thermal transferability, thus demonstrating higher heat absorption and dissipation rates. Finally, the asphalt mixtures containing PCMs showed lower mechanical performance than the control mixtures. However, they still satisfy the required criteria. In any case, it is expected that with the incorporation of PCMs into asphalt pavements, the social and environmental effects (Urban Heat Island) of sunlight in urban areas can be mitigated by the thermoregulation phenomena.